Intelligence and the ‘War against Terrorism’: Multilateral Counter-Terrorism Policies Implemented post-September 11 - Fulton, Wayne (My University, 2006)
The events of September 11 (9/11) have proved to be the catalyst for the evolution of ‘traditional’ terrorism methodologies into those of a transnational dimension. As a consequence, 9/11 has reshaped the international security community’s perceptions regarding the transnational threat of terrorism. Security analysts have called for a ‘networked’ response as the most effective strategy of defence against global terrorist networks. Hence, efforts to contain the threat of transnational terrorism will be more effective if implemented in conjunction with policies and mechanisms designed to facilitate international counter-terrorism co-operation. Therefore, taking into account the ‘perceived’ intelligence failure of 9/11, intelligence and anti-terrorism law enforcement agencies of governments committed to the ‘war against terrorism’ will need to integrate their intelligence capabilities and establish operational co-ordination on a multilateral level as an effective counter-terrorism mechanism. This research will focus on the multilateral intelligence sharing and counter-terrorism co-ordination mechanisms implemented post-9/11 by governments and International Organisations, such as the UN’s Counter Terrorism Committee and NATO’s invoking of Article 5, to contain and confront transnational terrorism. It is not within the scope of this study to analyse the reasons and ideologies behind 9/11 and modern-day terrorism.
Master of Arts - International Relations
Keywords: internaional regime theory; multilateralism; counter-terrorism policies; co-operative security theory; intelligence; international terrorism